1
1*1*1*1*1+1=4 divided by4
1.66666666666666666667 because 3 plus 1 plus 1 equals 5 and 5 divided by 3 equals 1.6666666666666666666.7.
x = 5, y = -1
That factors to (a + 1)(a + b) a = -1, -b b = -a
1
-1 plus 1 = 0 plus 1 =1
1*1*1*1*1+1=4 divided by4
a+a=1 2a=1 a=1/2
1.66666666666666666667 because 3 plus 1 plus 1 equals 5 and 5 divided by 3 equals 1.6666666666666666666.7.
(3x + 1) = -3 (x + 2x -1) (3x + 1) = -3 (3x - 1) 3x + 1 = -9x + 3 12x = 2 6x = 1 x = 0.16666666666666666666666666666666666666666666666666666666666666666666
i have no clue what the answer is
x = 5, y = -1
That factors to (a + 1)(a + b) a = -1, -b b = -a
-1
4/x - 1 + 6/3x +1 = 15/3x + 1 4/x - 1 + 2/x +1 = 5/x + 1 4/x + 2/x - 5/x = 1 + 1 -1 1/x = 1 x = 1
A = 1, B = 9